(untitled) (Social Science Review, 2024)
The global COVID-19 pandemic has adversely affected maternal and child health services and is likely to undermine the performances achieved in the last few decades. This study tried to identify the effects of COVID-19 on maternal, neonatal, and child health services including both home and facility delivery, antenatal and postnatal care, and births and deaths of neonates and mothers. Using secondary data of the 64 districts of Bangladesh from 2016 to 2020 (available at the Directorate General of Family Planning (DGFP) website), this study compared the data of 2020 with the average of 2016-2019 and analyzed the trends for several indicators from 2016 to 2020. Finally, a regression was performed to identify the determinants of facility delivery and the effects of COVID-19 on 4 ANCs. The study finds a declining trend in major indicators for maternal, neonatal, and child health services during the COVID-19 pandemic compared with the average of years 2016 to 2019. More specifically, during that period antenatal cares (ANCs) and post-natal cares (PNCs), home delivery with and without a trained person declined whereas facility delivery increased. Regression estimates a 5.3% decline in facility delivery in the districts with more than average COVID-19 cases (1,241 cases) compared to the districts with below-average COVID-19 cases. There was a significant (p = 0.0014) difference of 8.50% in facility delivery between the districts with above-average cases and below-average cases. The estimates may offer some guidance on how countries should react to such a pandemic to ensure continuity of care with adequate funding for prevention and control measures, supplies and services, and required equipment for healthcare workers, even though the study did not aim to project the post-COVID-19 effects. Social Science Review, Vol. 40(2), December 2023 Page: 171-184